2002
DOI: 10.1002/joc.767
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of summer‐ and winter‐time suburban energy fluxes in Christchurch, New Zealand

Abstract: Knowledge of the surface energy balance is fundamental to understanding the boundary layer meteorology and climatology of urban areas. This study reports some of the first direct measurements of energy fluxes over the city of Christchurch, New Zealand, during both summer and winter. Observations of the surface energy balance were made over two mainly residential suburbs: St Albans and Beckenham. Net all-wave radiation Q * was measured with a net radiometer, the eddy covariance approach was used to measure the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 14 publications
3
24
0
2
Order By: Relevance
“…In fact, the values obtained by the scintillometer which are used to calibrate k B −1 are definitely typical of measurements over this type of surface in winter and early spring. Spronken-Smith [44], in a study of energy fluxes over a suburban area in New Zealand, reports ensemble means of sensible heat flux peaking at 50-60 W/m 2 between 12:00 and 14:00 for the middle of winter. Grimmond [17] reports slightly higher values over a suburb of Vancouver for measurements taken in January and February.…”
Section: Determination Of the Thermal Roughness Lengthmentioning
confidence: 99%
“…In fact, the values obtained by the scintillometer which are used to calibrate k B −1 are definitely typical of measurements over this type of surface in winter and early spring. Spronken-Smith [44], in a study of energy fluxes over a suburban area in New Zealand, reports ensemble means of sensible heat flux peaking at 50-60 W/m 2 between 12:00 and 14:00 for the middle of winter. Grimmond [17] reports slightly higher values over a suburb of Vancouver for measurements taken in January and February.…”
Section: Determination Of the Thermal Roughness Lengthmentioning
confidence: 99%
“…In urban and suburban areas, vegetation cover has been shown to be important for explaining spatial differences in urban and suburban evapotranspiration rates (Grimmond and Oke 1999;Spronken-Smith 2002), net CO 2 exchange (Soegaard and Møller-Jensen 2003;Moriwaki and Kanda 2004), and microclimate characteristics (Bonan 2000;Byrne et al 2008;Huang et al 2008). For example, Spronken-Smith (2002) found that residential neighborhoods in Christchurch, New Zealand with high vegetation cover had greater evapotranspiration rates than did neighborhoods with less vegetation cover.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Spronken-Smith (2002) found that residential neighborhoods in Christchurch, New Zealand with high vegetation cover had greater evapotranspiration rates than did neighborhoods with less vegetation cover. Grimmond and Oke (1999) showed that the variability among North American cities in evapotranspiration rates was related to differences in the percent cover of vegetated surfaces, in addition to differences in precipitation and irrigation inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent urban energy balance observations have also been conducted in other parts of the world, including Basel in Switzerland (Rotach et al 2005), Lódź in Poland (Offerle et al 2005a), Edinburgh in Scotland (Nemitz et al 2002), Christchurch in New Zealand (Spronken-Smith 2002), Tokyo in Japan (Moriwaki and Kanda 2004), Marseille in France (Mestayer et al 2004;Grimmond et al 2004b) and the west African Sahel: Ouagadougou in Burkina Faso (Offerle et al 2005b). Together, these studies document the temporal and spatial variability of energy flux partitioning in more densely built-up, old suburban residential locations with mature, tall tree canopies that are generally higher than the buildings and in downtown areas or central city sites (densely built-up area, low vegetation cover, tall buildings with massive walls and deep street canyons).…”
Section: Introductionmentioning
confidence: 99%